Disease cause attribution and preference for low versus high self-management treatments - Tom Joonhwan Kim; Jaehwan Kim (Scientific Reports)
Abstract We investigate how disease cause attribution influences preferences for treatments that vary in patients’ self-management by comparing the attribution of disease cause to lifestyle and attribution to genes. We demonstrate that individuals’ self-control trait is a critical moderating factor in deciding preference between treatments in response to the disease cause information. Individuals with low self-control traits had a stronger tendency to prefer a treatment that requires a low level of self-management when they attributed the disease cause to genes than when they attributed it to their lifestyle. However, the preference for treatments of individuals with high self-control traits was not influenced by the disease-cause attribution. We suggest medical practitioners consider how disease attribution can influence preference for available treatment options when communicating with their patients.